Penerapan Aplikasi Akuntansi pada UMKM - Nurhasanah, Siti; Santoso, Wahyu Purbo; Puri, Pustika Ayuning (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study examines the crucial role of accounting applications in supporting the success of Micro, Small, and Medium Enterprises (MSMEs) in the contemporary business landscape, rife with challenges. Amidst global competition and financial intricacies, accounting applications have emerged as a pivotal tool for optimizing corporate governance, enhancing transparency, and attaining added value and investor interest. Previous research underscores the positive impact of accounting applications on operational efficiency, prudent tax avoidance, and profit augmentation. This study designs and implements a specialized accounting application tailored for MSMEs, offering essential features such as transaction recording, user management, financial reporting, inventory management, and risk mitigation. However, the effective adoption of this application hinges upon proper understanding and training for MSME owners. This research encapsulates the significance of accounting applications in fostering sustainable growth for MSMEs and achieving success in a dynamic business environment.